Karakter Fiksi ‘Si Unyil’ Sebagai Objek Perlindungan Hak Cipta di Indonesia - Medinah, Andi Sabriani (Fakultas Hukum Universitas Islam Indonesia, 2018)
Fiction character is the depiction of the character of a story character who is turned on and controlled by the author himself. Fiction characters themselves are basically a form of ideas expressed either by writing or drawing. However, the idea must be realized in real form to obtain copyright protection. The basic concept of the Copyright law is that copyright only protects creation that can be read, heard, or seen by others. Reviewed Law No.28 of 2014 about copyright law, the regulation regarding the protection of fictional characters has not been independently regulated, that is, a fictional character has its own copyright without having to be in a copyrighted work. Based on the elements of a work considered as a creation in Article 1 numbers 2 and 3 of copyright law, fictional characters can be used as objects of copyright protection. Based on copyright law, legal protection for character creation can be done through recording, agreements, licenses, alternative dispute resolution, arbitration, or through litigation.